Students' numeracy literacy skills and mathematical habits of mind: A diagnostic analysis - Taruli Silalahi; Izwita Dewi; Faiz Ahyaningsih (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2026)
This study aims to conduct a diagnostic analysis of students by mapping their numeracy literacy (NL) and Mathematical Habits of Mind (MHOM) profiles, as well as examining the relationship between the two in solving non-routine problems. A mixed methods approach with a cross-sectional diagnostic design was employed, involving 120 elementary school students from three schools. Data were collected through a numeracy literacy diagnostic test, an MHOM questionnaire, structured observations, and in-depth interviews. The results indicate that students’ numeracy literacy ability falls into the moderately low category, with an average mastery percentage of 46.13%. The main weakness was found in the interpreting process, with a mastery percentage of 34.45%, while students showed relatively better performance in the applying process. The MHOM profile was in the moderate category, with relatively high scores in perseverance and working accurately, but low scores in seeking patterns and flexible thinking. The correlation analysis revealed a significant positive relationship between overall numeracy literacy and Mathematical Habits of Mind (r = 0.582, p < .001). Qualitative findings further showed that students with weak flexible thinking tended to repeat ineffective procedures when facing unfamiliar or non-routine problems. These findings indicate that students’ numeracy literacy difficulties are not only related to content mastery but also to dispositional barriers, particularly limited flexible thinking. This study contributes by providing a diagnostic mapping that links numeracy literacy difficulties with students’ Mathematical Habits of Mind. The findings suggest that instructional interventions should strengthen flexible thinking and pattern seeking to support students’ functional numeracy literacy.